Resource use associated with type 2 diabetes in Asia, Latin America, the Middle East and Africa: results from the International Diabetes Management Practices Study (IDMPS) - Ringborg, A. (2009)
Aims: To estimate diabetes-related resource use and investigate its predictors among individuals with type 2 diabetes in 24 countries in Asia, Latin America, the Middle East and Africa. Methods: Cross-sectional observational data on diabetes-related resource use were collected from 15,016 individuals with type 2 diabetes within the second wave of International Diabetes Management Practices Study. Mean (SD) annual quantities were determined and predictors of diabetes-related hospitalisations, inpatient days, emergency room visits and absenteeism were investigated using negative binomial regression. Results: Patients in Asia (n = 4678), Latin America (n = 6090) and the Middle East and Africa (n = 4248) made a mean (SD) of 3.4 (6.9), 5.4 (6.7) and 2.5 (4.4) General Practitioner visits per year. The mean (SD) number of inpatient days amounted to 3.8 (18.1), 2.2 (13.9) and 2.6 (13.5) per year. Results of the regression analysis showed the major influence of diabetes-related complications and inadequate glycaemic control on resource use. The expected annual rate of hospitalisation of patients with macrovascular complications compared with those without was 4.7 times greater in Asia [incidence rate ratio (IRR) = 4.7, 95% CI: 2.8-7.8, n = 2551], 5.4 times greater in Latin America (IRR = 5.4, 95% CI: 3.0-9.8, n = 3228) and 4.4 times greater in the Middle East and Africa (IRR = 4.4, 95% CI: 2.8-6.9, n = 2630). Conclusions: Micro- and macrovascular complications and inadequate glycaemic control are significant predictors of resource use in people with type 2 diabetes of developing countries. This knowledge confirms the health economic importance of early diagnosis of diabetes, education of patients and glycaemic control.